2017
DOI: 10.1080/13854046.2017.1368715
|View full text |Cite
|
Sign up to set email alerts
|

Performance on the Test of Memory Malingering is predicted by the number of errors on its first 10 items on an inpatient epilepsy monitoring unit

Abstract: TOMMe10 shows great promise in predicting future TOMM performance. In settings where time with patients is at a premium, ≥2 errors on TOMMe10 may be used as an early TOMM discontinue criteria, allowing examiners to use their limited time more effectively. The use of TOMMe10 in settings with varying TOMM failure base rates was discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…T1 has also shown comparable classification accuracy and psychometric properties to that of T2, when used following T1, even though T1 alone has a briefer administration time and reduces patient burden (Martin et al, 2020; Ovsiew et al, 2021). Additionally, T1e10 (i.e., the first 10 items of T1) has received increasing attention in the PVT literature, given its potential as another, even further abbreviated index from the TOMM (Denning, 2021; Grabyan et al, 2018; Kulas et al, 2014). Nonetheless, in direct comparisons of T1 and T1e10, T1 has evidenced superior accuracy, perhaps because T1e10 has shown a higher rate of false positive errors than T1 for patients with severe memory impairment (Cohen et al, 2021; Kraemer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T1 has also shown comparable classification accuracy and psychometric properties to that of T2, when used following T1, even though T1 alone has a briefer administration time and reduces patient burden (Martin et al, 2020; Ovsiew et al, 2021). Additionally, T1e10 (i.e., the first 10 items of T1) has received increasing attention in the PVT literature, given its potential as another, even further abbreviated index from the TOMM (Denning, 2021; Grabyan et al, 2018; Kulas et al, 2014). Nonetheless, in direct comparisons of T1 and T1e10, T1 has evidenced superior accuracy, perhaps because T1e10 has shown a higher rate of false positive errors than T1 for patients with severe memory impairment (Cohen et al, 2021; Kraemer et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Cohen and colleagues (2021) also highlighted the low sensitivity of T1e10 to detect invalid performance and cautioned against its use with patients exhibiting severe memory impairment. However, other researchers have cited relatively high sensitivity for this measure in cross-validation studies (74-89% with acceptable specificity of ≥90%; Denning, 2021;Kraemer et al, 2020;Grabyan et al, 2018). Given equivocal findings across different studies in the extant literature, we retained individuals with severe memory impairment in our sample to increase the generalizability of our findings to different clinical settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burgeoning empirical investigations now support abbreviating freestanding PVTs to increase efficiency in neuropsychological evaluations while maintaining the incremental diagnostic accuracy for invalid performance commonly provided by freestanding measures. The TOMMe10—a substantially abbreviated administration of one of the most commonly used PVTs—is one such indicator that has been validated in multiple clinical populations (Denning, 2012; Grabyan et al, 2018; Loughan et al, 2016), though existing research has largely validated this indicator against the TOMM itself or PVTs with more limited diagnostic accuracy. The current study sought to build evidence for the TOMMe10 by evaluating the convergent, discriminant, and concurrent validity of TOMMe10 performance with some of the most diagnostically accurate PVTs in a mixed clinical sample.…”
Section: Discussionmentioning
confidence: 99%
“…Although sensitivity on the TOMMe10 was lower than TOMM T1, both measures had similar negative predictive values for the overall TOMM. On an inpatient epilepsy monitoring unit, Grabyan, Collins, Alverson, and Chen (2018) found that a cutoff of ≥2 errors optimized sensitivity (.88) and specificity (.93) when TOMM T1 and TOMM T2 were used as criterion. When TOMMe10 was compared to other PVTs (e.g., Word Memory Test; Green, 2005; Wechsler Adult Intelligence Scale, 4th ed.…”
mentioning
confidence: 99%